Teaching and learning chemistry through the situational approach: Analysis and perspective, case of schools in Lubumbashi in the Democratic Republic of Congo. - Kasongo Nasser,; Mutombo Hulumba.P,; Kamand Yitil,; Muleba Mvita .C, (IJRDO- Journal of Educational Research, 2024)
The objective of this work was to verify the effectiveness of the practicability of the approachthrough situations in schools in this educational area. This study concerned 36 teachers wholed the chemistry course in first scientific humanity and at the same time in the 8th basiceducation class, 180 students and parents of these students. After analyzing the data using thechi-square test and Fisher's Z test, the set of results indicates the absence of chemistryequipment, the insufficiency of experimental practice by the students, there was question ofthe demonstration during some rare manipulations and the contributions of the situation-basedapproach were not found among the students. The multiplication of training in Approachthrough situations and the collaboration between teachers and artisans exploiting the notionsof chemistry found in the learners' environment for the contextualization of chemistry remainthe strong points to be encouraged.